Clerical Conceptions of Magic and the Stereotype of the Female Witch - Moebius, Matthew Alexander (My University, 2011)
Working from the foundation laid by leading historians of medieval witchcraft -- most notably Richard Kieckhefer, Norman Cohn, Michael Bailey, and Hans Peter Broedel -- this study examines the conceptual development of a predominantly feminine witchcraft stereotype as understood within the perceptions of the educated clerical elite. The theories of these historians, each approaching the study of witchcraft in different ways and addressing mostly separate aspects of the phenomenon, are reconciled with one another and tied together in hitherto unarticulated ways to form a single, cohesive narrative of the emergence of the idea of the exclusively female witch. The gradual evolution of clerical conceptions of magic shifted in the later Middle Ages from a masculine conception to a more gender-neutral one, opening the door to feminization. The construction of the witches' sabbat, influenced by largely feminine pagan mythological motifs, pushed the idea in the direction of a female conception. Finally, influential writings dominated by aggressively misogynistic ideology finalized the association between women and witchcraft.
Keywords: Medieval witchcraft; Mythology; Magic; Witch